Mediamorphosis in Kompas TV towards New Media - Ramadoni, Muhamad Afdoli; Hayat, Vina Zahratul; Noor, Sihabudin; Prasetyo, Eko Yudi (Jurnal Ilmiah Syi'ar, 2022)
This study aims to determine the media transformation carried out by Kompas TV using the concept of mediamorphosis, which Roger Fidler initiated. The question in this research is how is the process of coevolution, convergence, and complexity in Kompas TV. This type of research is qualitative and uses content analysis. The object of this research is Kompas TV communication media accessed through kompas.tv.com. This study indicates that Kompas TV has changed its image and brand and provides digital optimization and automation services with quality, fast and safe artificial intelligence technology. So that it is a virtual product provider connected to PPOB that a broad audience can access. Kompas TV carries out media convergence activities: co-optation by combining print information technology and electronic media with analog formats into digital. In business, this corporate merged between Kompas Gramedia and PT. Trans Corporation in share ownership of PT. Cipta Megaswara Television. There is a change in habits in today's society from the conventional way of reading newspapers and watching television broadcasts to an instant and fast way by utilizing the development of digital technology.